Heirlooms and Heritage : Unveiling the Cultural Narratives of the Orang Ulu - Yvonne Michelle, Campbell; Remmy, Gedat; Jamilah, Maliki; Elexson, Nillian (2024)
Family heirlooms are cherished objects passed down through generations, often accompanied by stories and narratives that hold significant value for families. However, these heirlooms can be lost due to various factors, such as family disputes, natural disasters, or wars. This case study examines the family heirlooms of three Orang Ulu individuals and explores the rich stories behind them. The heirlooms presented include traditional Orang Ulu beads and an iron belt. Interviews with these individuals reveal that each heirloom, inherited from their grandparents, carries a unique story that enhances its cultural and sentimental significance. These heirlooms not only represent priceless artifacts but also embody the connection to the cultural practices, rituals, and traditions of the Orang Ulu people. This study also highlights that many traditional Orang Ulu crafts, especially beads, are often commodified in the modern market, potentially disconnecting them from their rich cultural heritage. Thus, preserving these heirlooms and the narratives surrounding them is vital in maintaining the cultural identity of the Orang Ulu community.